Faustino Aizkorbe: public sulpture in Navarre - Muruzábal del Solar, José María (Huarte de San Juan. Geografía e Historia, 2009)
The current article goes through the figure of the sculptor Faustino Aizkorbe from Navarre (Olloki, Navarre, 1948), without any doubts the most distinguished current sculptor of Navarre, and the one who has become a figure of national and international renown. Versatile artist, his sculpture, related to the Basque School of Sculpture, can always be categorized as belonging to abstraction. In the article it contributes with a note of his biography, with the most outstanding highlights, a summary of the most notable characteristics of his work, and it analyzes the public sculpture which the author has put up in the Foral Community of Navarre. It includes the whole catalogue of its work, with photographs, technical specifications, and a brief commentary of each of its pieces. The collection turns out to be of great relevance insofar as it is compound of 45 sculptures, worked between 1979 and 2009.
Keywords: Faustino Aizkorbe; sculptor; sculpture; abstraction; biography